Study on the Mechanical Properties of Red Clay under Drying-Wetting Cycles - Yanli Qi; MingZhou Bai; Hao Zhou; Hai Shi; Pengxiang Li; Bohu He (Advances in Materials Science and Engineering)
To study the mechanical properties of red clay under repeated dry and wet cycle test conditions, in this paper, the disturbed red clay in an engineering area in Liuzhou, Guangxi Province, was taken as the research object. By artificially controlling different dry and wet cycles in the laboratory, a direct shear test and triaxial consolidation drainage test were carried out on the red clay samples after different dry and wet cycles. The stress-strain curve and change rule of corresponding c and φ values were obtained. The results showed that, in both the direct shear test and the triaxial test, the shear strength parameters of red clay decreased with an increase in the number of dry and wet cycles and the attenuation was most obvious during the first cycle. With an increase in the number of dry and wet cycles, the attenuation gradually decreased. The constitutive model of the deviatoric stress and strain curve of red clay under dry and wet cycles was a plastic-hardening type. By analyzing the variation in parameters in the P-H model, the relationship between c, φ, and the number of dry and wet cycles n was obtained. The results showed that the parameters had different degrees of attenuation with the action of dry and wet cycles. To explain the above rules, some samples under different drying-wetting cycles were selected for environmental electron microscope scanning, and appropriate assumptions were made based on the microstructure.